2015
DOI: 10.4238/2015.october.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness evaluation of dendritic cell immunotherapy for osteosarcoma on survival rate and in vitro immune response

Abstract: ABSTRACT. The aim of this study was to investigate the effects of dendritic cell (DC) therapy in osteosarcoma. Bone marrow DCs from Wistar (allograft group) and Sprague Dawley (SD) (homograft group) rats were electrically fused with the SD-derived osteosarcoma cell line UMR106 to generate a DC-osteosarcoma fusion (DOF) tumor vaccine, which was co-incubated with SD T lymphocytes to stimulate T cell proliferation. CD8+ and CD4+ cell percentages were measured by flow cytometry; tumor-cytotoxic effects of cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Presence of a second APC, CD1a+ DCs, is also associated with poor survival in osteosarcoma. With the recent advent of DC vaccines as a cancer treatment, multiple groups have shown that DC vaccines have varying levels of effectiveness in animal models of osteosarcoma 51 52 53 54 . It has been previously shown that human osteosarcoma cells in culture inhibit the ability of DC to present antigens 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Presence of a second APC, CD1a+ DCs, is also associated with poor survival in osteosarcoma. With the recent advent of DC vaccines as a cancer treatment, multiple groups have shown that DC vaccines have varying levels of effectiveness in animal models of osteosarcoma 51 52 53 54 . It has been previously shown that human osteosarcoma cells in culture inhibit the ability of DC to present antigens 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous immunotherapies were assessed to modulate the tumor microenvironment and to reactivate a prolonged and efficient immune response [6]. Adoptive cell therapies based on TIL as described above and generating antigen-specific lymphocytes [103][104][105], dendritic cells [106][107][108][109][110][111][112], NK cells [113][114][115][116][117][118] were developed mostly in vitro and in pre-clinical model of osteosarcoma. Several clinical trials are currently in progress for evaluating their therapeutic efficacy in patients (Table 1).…”
Section: Lymphocytes Subpopulations In Osteosarcoma and Therapeutic Imentioning
confidence: 99%
“…Effective anti-cancer therapies alone or in combination have thus been designed in bone sarcomas to stimulate tumor-associated dendritic cell function as a means of driving the antitumor immune response and preclinical results showed promising results [Li et al, 2019;He et al, 2016;Fang et al, 2015;Kawano et al, 2015]. Clinical investigations did not confirm the results of pre-clinical studies.…”
Section: Dendritic Cells For Improving the Immune Recognition Of Bonementioning
confidence: 99%
“…Bone sarcomas expressed specific antigens (Table 1), which have stimulated the development of targeted therapies. Effective anti‐cancer therapies alone or in combination have thus been designed in bone sarcomas to stimulate tumour‐associated dendritic cell function as a means of driving the anti‐tumour immune response and preclinical results showed promising results (Fang, Jiang, & Xia, 2015 ; He, Zhang, Kou, & Tang, 2016 ; Kawano et al, 2015 ; Li, Wang, & Fang, 2019). However, clinical investigations did not confirm the results of preclinical studies.…”
Section: Dendritic Cells For Improving the Immune Recognition Of Bone Sarcoma Cellsmentioning
confidence: 99%